Dual-Band Balanced-to-Unbalanced Power Divider With Independent Power Division Ratios - Zihui Zhu; Zhongbao Wang; Jian Ma; Hongmei Liu; Shaojun Fang (IEEE Access, 2020)
A dual-band balanced to unbalanced power divider with independent power division ratios (PDRs) at two operating frequencies is proposed in this article. The proposed power divider includes a dual-band phase inverter, a grounded resistor, and four transmission-line sections (TLS). By simultaneously changing characteristic impedances and electrical lengths of the four TLS, the independent PDRs are obtained, and the large-signal output port at lower and upper operation bands can be different. Compared to the previous works, it has more flexibility in the power division. Moreover, the closed-form design equations are provided and discussed. To verify the proposed structure, two BTU power dividers operating at 1.0 and 2.0 GHz are designed, fabricated, and measured. The PDRs of the first power divider are -6 and 6 dB for the lower and upper operation bands, respectively. The second power divider has the PDRs of 3 and -6 dB. The measured results are good agreements with the theoretical calculation and electromagnetic simulation.